Analisis Pertumbuhan Ekonomi dan Dampaknya Terhadap Tingkat Pengangguran Terbuka dan Angka Kemiskinan Kota Manado Tahun 2014 – 2023 - Andar Mangerbang Pehulisa Ginting; Vecky A.J Masinambow; Agnes L.Ch.P. Lapian (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to determine the effect of economic growth on the open unemployment rate, the effect of economic growth on the poverty rate, the effect of the open unemployment rate on the poverty rate and the effect of economic growth on the poverty rate through the open unemployment rate in Manado City. The data used in this research is secondary data with an observation period of 10 years, namely 2014-2023, obtained from the Manado City Central Statistics Agency. The analytical method used in this research is path analysis. The results of the research show that economic growth has a negative and insignificant effect on the open unemployment rate, economic growth has a positive and significant effect on the poverty rate, the open unemployment rate has a positive and significant effect on the poverty rate and economic growth has a positive effect on the poverty rate through the open unemployment rate as a variable intervening.